Laser-directed synthesis of strain-induced crumpled MoS2 structure for enhanced triboelectrification toward haptic sensors. (December 2020) - Park, Seoungwoong; Park, Jiseul; Kim, Yeon-gyu; Bae, Sukang; Kim, Tae-Wook; Park, Kwi-Il; Hong, Byung Hee; Jeong, Chang Kyu; Lee, Seoung-Ki
Abstract: Two-dimensional (2D) transition metal dichalcogenide (TMDC) nanomaterials are currently regarded as next-generation electronic materials for future flexible, transparent, and wearable electronics. Due to the lack of compatible synthesis and study, however, the characteristic influences of 2D TMDC nanomaterials have been little investigated in the field of triboelectric nanogenerator (TENG) devices that are currently one of the main technologies for mechanical energy harvesting. In this report, we demonstrate a fast, non-vacuum, wafer-scale, and patternable synthesis method for 2D MoS2 using pulsed laser-directed thermolysis. The laser-based synthesis technique that we have developed can apply internal stress to MoS2 crystal by adjusting its morphological structure, so that a surface-crumpled MoS2 TENG device generates ~40% more power than a flat MoS2 one. Compared to other MoS2 -based TENG devices, it shows high-performance energy harvesting (up to ~25 V and ~1.2 μA) without assistance from other materials, even when the counterpart triboelectric surface has a slightly different triboelectric series. This enhanced triboelectrification is attribute to work function change as well as enlarged surface roughness. Finally, the direct-synthesized MoS2 patterns are utilized to fabricate a self-powered flexible haptic sensor array. The technique we propose here is intended to stimulate further investigation of the triboelectric effects and applications of 2D TMDC nanomaterials. Graphical abstract: Image 1 Highlights: Fast, non-vacuum, large-scale and patternable synthesis of 2D MoS2 is developed by laser-directed thermolysis. Surface morphology of MoS2 is intentionally controlled by tuning laser synthesis mechanism. Surface-crumpled MoS2 shows high-performance triboelectric energy harvesting signals. Improved triboelectrification is attributable to work function change, surface area enlargement, and secondary effects. Self-powered flexible haptic sensor array is fabricated using directly patterned MoS2 .